Enhanced Payload Data Reduction Approach for Cluster Head (CH) Nodes - N. A. M. Alduais; J. Abdullah; A. Jamil (Universitas Ahmad Dahlan, 2017)
In this paper, we suggested two approaches to minimizing the CH packet size by considering the accuracy of prediction of sensed data at the base station. The proposed coding schemes based relative difference (CS-RD) and based the factor of precision (CS-FP) instead of the absolute change method that has been used in recent work. The aim is to enhance the accuracy of prediction data at the base station. Therefore, the performance metric was evaluated in term of the accuracy of prediction data at the base station. Simulation results showed that the proposed approaches performed better in term of the accuracy of prediction data at the base station. Specifically, the distortion percentage and average Absolut error in the CS-RD and CS-FP method decreased by 50% and 88% better than the current new aggregation method (ADATDC). However, our proposed CS-FP showed a low reduction ratio for some states.